MODEL BANGKITAN PERGERAKAN PENDUDUK DI KABUPATEN ACEH BARAT DAYA BERDASARKAN STRUKTUR RUMAH TANGGA DAN PENDAPATAN KELUARGA - Akbar Hikmi; Renni Anggraini; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The district of Aceh Barat Daya has 9 sub-districts, of which there are 3 sub-districts with the highest population, Susoh, Blangpidie and Kuala Batee. Increasing population in the sub-district, resulting in an increase in the number of transport movements that will affect road capacity. It is therefore necessary to model a revival of the movement in the sub-district, living in the area on the basis of its activity. Movement activity has 2 categories, namely mandatory and non-mandatory activities. Mandatory activity is the work and school activities undertaken by individuals, while non-mandatory activities are activities such as daily shopping, shopping that is not done daily, carrying and delivering children or other people, as well as other activities such as recreation, social visits, and other entertainment activities. This study aims to find out the pattern of the rise of household travel, based on the structure and income of the family in terms of mandatory and non-mandatory activities in Blangpidie, Susoh and Kuala Batee sub-districts. The results showed that in mandatory activity there was only 1 best model, that is in movement of family structure greater than 2 children (Y2.a = -0,427 + 0,296X2 + 0,341X7). In this case the factors that influence the rise of movement of family structure on mandatory activity is the age factor and the number of motorcycle in the family. In non-mandatory activity there are 2 best model, that is in movement of family structure greater than 2 child (Y2.b = -1,128 + 0,972X2 + 1,651X3) and movement of family income greater than 3 million (Y4.b = -1,475 + 0,940X2 + 2,553 X3). In this case the factors that influence the rise of movements of family structure and income in non-mandatory activities is the factor of age and level of education.